PENGARUH SIKAP ILMIAH TERHADAP HASIL BELAJAR DAN KEMANDIRIAN BELAJAR MELALUI STRATEGI SCAFFOLDING-KOOPERATIF - Merta Dhewa Kusuma; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
The purposes of this study to find out: (1) the influence of the student’s scientific attitude to the learning achievement of students through scaffolding-cooperative strategy; (2) the influence of the student’s scientific attitude to the learning independence of students through scaffolding-cooperative strategy. The population and the sample of this study are all students of XI IPA classroom of Tunas Harapan Bandar Lampung Senior High School in the second semester, and there are 20 students. Sample class is selected by purposive sampling. Design of this study is one-shot case study design. The results of this study are: (1) there is influence of the student’s scientific attitude to the learning achievement of students through scaffolding-cooperative strategy; (2) there is influence of the student’s scientific attitude to the learning independence of students through scaffolding-cooperative strategy. The average percentage of the student’s scientific attitude is 67% with the high category. The average value of the student learning is 66 with the high category. While, the average percentage of the student’s independence is 66% with the high category. Thus, the high of scientific attitude can affect the student’s learning achievement and student’s learning independence.Keyword: scientific attitude, learning achievement, learning independence, scaffolding-cooperative strategy.